RETHINKING AUTHORITY AS APPARATUS OF CONTROL IN BUREAUCRATIC INSTITUTIONS IN NIGERIA - Eboh, Emmanuel A (African Journal of Social and Behavioural Sciences, 2019)
This paper examines the propriety of the use of legitimate authority as a tool of control in the Nigerian governance space. The exercise of Authority commands the recognition of the moral right to demand obedience. In Nigeria, it seems the reverse is the case. Those in „Authority‟ exercise power over the ruled, and achieve obedience through the fear of coercion. This has engendered low productivity, power intrigues and pervasive flouting of rules and order. It has also resulted to loss of material, human and social disequilibrium. This situation has called for a rethinking of the efficacy of the authority structure as an appropriate instrument of control in Nigerian institutions. This work adopts the qualitative research design. Max Webers ideal type bureaucracy theory was utilized as theoretical framework. The methodology is purely analytical and relies on existing literature for data. Our findings include: most people in „authority‟ positions attained them through primordial considerations; Corruption has weakened the fabrics of many of the institutions of authority; ethnicity, Nepotism and the politicization of public bureaucracy has encouraged the promotion of some public officers to their level of incompetence among others. Recommendations include; Building faith in the legitimacy of the system through institutional reforms; Anti-corruption war should be prosecuted without fear or favour. This would expose corrupt public office holders, while assuaging the public that justice is been done. It would also serve as deterrent to potential culprits; the electorates to utilize the mechanism of „recall‟ to checkmate erring political office holders; neutral competence and Bureaucratic responsiveness; among others.